The Latino Migration Experience in North Carolina : New Roots in the Old North State - Gill, Hannah E. (Hannah Elizabeth), 1977- (Book collections on Project MUSE., 2010)
Over recent decades, the Southeast has become a new frontier for Latin American migration to and within the United States, and North Carolina has had one of the fastest growing Latino populations in the nation. Here, Gill offers North Carolinians from all walks of life a better understanding of their Latino neighbors, bringing light instead of heat to local and national debates on immigration.